Pola Relasi Muhammadiyah dengan Masyumi, Parmusi dan PAN - Suwarno, Suwarno (Jurnal Review Politik, 2019)
This study aims to reveal the pattern of Muhammadiyah relations with three political parties, namely Masyumi, Parmusi and PAN. In this study, the author fully used the historical research method, which can be divided into four steps. First, heuristics or collection of primary and secondary sources that will be centered in the Muhammadiyah Central Leadership Library (PP), Yogyakarta Regional Library, and Yogyakarta Regional Archives. Second, source criticism includes external criticism to test authenticity and internal criticism to find out the credibility of the source. Third, interpretation or interpretation of historical facts generated from the second step by carrying out analysis and synthesis. Fourth, historiography or writing of historical works. The results of the study indicate the similarity of the relationship between Muhammadiyah and Masyumi, Parmusi and PAN. This equation appears in the equal as a midwife who gave birth to the three parties. However, there is a slight difference. In the birth of Masyumi and Parmusi, Muhammadiyah acted as a midwife formally or directly. On the contrary in the birth of PAN, Muhammadiyah's position as an indirect or informal midwife in the birth of PAN. Meanwhile, the relationship between Muhammadiyah and Masjumi shows a pattern of ideological and organizational relations because Muhammadiyah is a special member of Masyumi. The pattern of Muhammadiyah's relationship with Parmusi shows only organizational and not ideological. Then the pattern of Muhammadiyah and PAN relations is not ideological and organizational because it is only informal. Thus, the pattern of Muhammadiyah and PAN relations follows a historical pattern - psychological, or only has cultural ties